Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1121/1.1850211
|View full text |Cite
|
Sign up to set email alerts
|

Effective impedance of surfaces with porous roughness: Models and data

Abstract: A “boss” formulation by Twersky [J. Acoust. Soc. Am. 73, 85–94 (1983)] enables prediction of the plane wave reflection coefficient from a surface composed of rigid-porous roughness elements embedded in an acoustically hard plane where the roughness elements and their mean spacing are small compared with the incident wavelengths. Predictions for air-filled porous roughness elements on a hard ground plane are compared with effective impedance spectra obtained from laboratory measurements over random distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…there is significant coherent scattering and reflection) there can be a significant change in ground effect. Many laboratory experiments have shown that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [38][39][40]91,92]. Particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: Ground Rougheningmentioning
confidence: 99%
See 1 more Smart Citation
“…there is significant coherent scattering and reflection) there can be a significant change in ground effect. Many laboratory experiments have shown that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [38][39][40]91,92]. Particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: Ground Rougheningmentioning
confidence: 99%
“…Several papers have reported laboratory data showing that the effect of adding small scale roughness to a surface, whatever its original impedance, is to modify its impedance [3,85,91,92,98]. If the original smooth surface is acoustically-hard then the effective impedance of the roughened surface is finite.…”
Section: Ground Rougheningmentioning
confidence: 99%
“…There is considerable laboratory data showing that the effect of adding small scale roughness to a surface, whatever its original impedance, is to modify its apparent impedance [2,[28][29][30][31][32]. If the original smooth surface is acoustically-hard then the effective impedance of the roughened surface is finite.…”
Section: Laboratory Data On 2d Rough Surfacesmentioning
confidence: 99%
“…there is significant coherent scattering and specular reflection) there can be a significant change in ground effect. Many laboratory experiments show that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [2,[28][29][30][31][32]. Also, particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: D Roughnessmentioning
confidence: 99%
“…This problem has attracted much attention in the literature (see, for example, [17,30,31,16,21,6,48]), both in its own right and also as a model of the scattering of an incident acoustic or electromagnetic wave by an infinite rough surface [8,47,36,7]. In the case in which there is no variation in the acoustical properties of the surface or the incident field in some fixed direction parallel to the surface, the problem is effectively twodimensional.…”
mentioning
confidence: 99%